Remote instrumentation services on the e-infrastructure applications and tools - Davoli, Franco (Springer, 2011)
This book focuses on all aspects related to the effective exploitation of remote instrumentation and to the building of complex virtual laboratories on top of real devices and infrastructures. These include service oriented architecture (SOA) and related middleware, high-speed networking in support of Grid applications, wireless Grids for acquisition devices and sensor networks, Quality Service (QoS) provisioning for real-time control, measurement instrumentation and methodology, as well as metrology issues in distributed systems.